2013
DOI: 10.1017/s0025315413000593
|View full text |Cite
|
Sign up to set email alerts
|

Physiological response of temperate microphytobenthos to freezing temperatures

Abstract: Microphytobenthos (MPB) contributes up to half the primary production of estuaries. These microorganisms are sensitive to changes in sediment temperatures, particularly the extreme temperatures during exposure periods. This study investigates the physiological responses of MPB to freezing temperatures at two locations near Hobart, Tasmania during winter. Photosynthetic parameters were measured at 2 mm intervals to a depth of 10 mm. FV/FM values at three different distances from the shoreline at Kings Beach and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Above 25°C, all photosynthetic parameters declined significantly, suggesting damage to the photosynthetic apparatus, while temperatures below the natural ambient minimum (~9.0°C) did not affect the photosynthetic activities. Since the MPB in Browns River naturally experiences temperatures below 0°C (Lee & McMinn, 2013) in winter, the MPB incubated at temperatures down to 0°C did not show any sign of photoinhibition, despite an increase in light levels. Similarly, Lee & McMinn (2013) found that the photosynthetic parameters (Water PAM) of MPB from Browns River were not adversely affected by freezing conditions.…”
Section: Discussionmentioning
confidence: 95%
“…Above 25°C, all photosynthetic parameters declined significantly, suggesting damage to the photosynthetic apparatus, while temperatures below the natural ambient minimum (~9.0°C) did not affect the photosynthetic activities. Since the MPB in Browns River naturally experiences temperatures below 0°C (Lee & McMinn, 2013) in winter, the MPB incubated at temperatures down to 0°C did not show any sign of photoinhibition, despite an increase in light levels. Similarly, Lee & McMinn (2013) found that the photosynthetic parameters (Water PAM) of MPB from Browns River were not adversely affected by freezing conditions.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, some of the variation could also have been caused by the fluorescence method itself and the duration of RLC exposure. For example, Lefebvre et al (2011) noted that α was systematically lower due to the slower relaxation of NPQ in 10 s RLCs.…”
Section: Effects Of Irradiance and Temperature Incubationsmentioning
confidence: 99%
“…The extent of photooxidative damage and the speed of recovery are related to the degradation rate of the D1 protein and the subsequent re-synthesis and replacement by new proteins (Derks and Bruce, 2018;Domingues et al, 2012). Similarly, benthic diatoms inhabiting sediment surfaces in estuaries are usually able to recover from extreme temperatures and light photoinhibition caused by tidal changes, since photoinhibition is only rarely recorded in these communities (Defew et al, 2004;Lee and McMinn, 2013;Perkins et al, 2006). Furthermore, many have the ability to migrate vertically, hence positioning themselves within the sediment at a depth that provides shading from excess irradiance and provides an optimal light environment for their photosynthetic activities (Cartaxana et al, 2011;Mouget et al, 2008;Perkins et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously examined the photophysiological response of MPB in Tasmanian coastal ecosystems to elevated light levels (Jordan and McMinn , Jordan et al. ) and extreme temperatures (Lee and McMinn ). Cook et al.…”
mentioning
confidence: 99%
“…We have previously examined the photophysiological response of MPB in Tasmanian coastal ecosystems to elevated light levels McMinn 2008, Jordan et al 2010) and extreme temperatures (Lee and McMinn 2013). Cook et al (2004) examined carbon and nitrogen cycling in a nearby mudflat and concluded that a significant proportion of the production was exported as DOC and EPS rather than cellular production.…”
mentioning
confidence: 99%